2009
DOI: 10.1063/1.3193664
|View full text |Cite
|
Sign up to set email alerts
|

Direct modulation of excited state quantum dot lasers

Abstract: The use of the excited state quantum dot lasers for high speed direct modulation is proposed and demonstrated. A direct comparison of lasers utilizing the ground state and excited state from the same laser material reveals a factor of two increase in the K-factor limited bandwidth. This is attributed to an increase in the saturated gain and reduced carrier scattering time of the excited state compared to the ground state.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
32
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 13 publications
3
32
0
Order By: Relevance
“…However, it has to be noted that the shapes of the gain spectra of both lasers may also affect the dynamics. 15,34 To this end, the ES laser under study might be more sensitive to optical feedback also because of a stronger modal competition as compared to the GS laser, which has a rather flat optical spectrum around the central lasing wavelength (not shown here). The different dynamics can also be attributed to the ES degeneracy where the existence of two closely spaced p-levels can lead to more radiative transitions.…”
Section: © 2016 Author(s) All Article Content Except Where Otherwismentioning
confidence: 99%
See 1 more Smart Citation
“…However, it has to be noted that the shapes of the gain spectra of both lasers may also affect the dynamics. 15,34 To this end, the ES laser under study might be more sensitive to optical feedback also because of a stronger modal competition as compared to the GS laser, which has a rather flat optical spectrum around the central lasing wavelength (not shown here). The different dynamics can also be attributed to the ES degeneracy where the existence of two closely spaced p-levels can lead to more radiative transitions.…”
Section: © 2016 Author(s) All Article Content Except Where Otherwismentioning
confidence: 99%
“…13 Owing to the faster carrier capture from the surrounding carrier reservoir as well as a higher saturated gain, 14 ES QD transmitters have been touted to be a promising solution for high-speed applications. 15,16 The larger degeneracy of the ES translates into a larger differential gain and smaller nonlinear gain compression than to those of the GS. The first successful investigation at the link level was realized with 1.…”
Section: © 2016 Author(s) All Article Content Except Where Otherwismentioning
confidence: 99%
“…22 The advantage of an ES laser is that the net modal gain is increased without increasing the QD layer number. Indeed, the scattering time is expected to be reduced 8 due to the higher density of final scattering states, leading to an increase in the predicted K-factor limited bandwidth (see Fig. 4, G sat ¼ 18 cm À1 , s 0 ¼ 3 ps, G sat ¼ 18 cm À1 , s 0 ¼ 1.5 ps).…”
mentioning
confidence: 99%
“…7 It has recently been demonstrated that operation using the excited state (ES) of the QDs exhibit much higher damping limited bandwidths as compared to ground state (GS) lasers. 8,9 This enhancement was attributed to higher saturated gain (double) and lower scattering time (half) compared to the ground state. However, this is achieved at the expense of higher operating currents and shorter operating wavelengths that may be impractical for fiber-optic based optical communications applications.…”
mentioning
confidence: 99%
“…Although a direct modulation rate of as high as 25 Gb/s for a GS lasing QD laser has been reported recently, there is still a large gap between practical and theoretical values. 4 On the other hand, the excited-state (ES) lasing QD lasers have recently shown to have greater modulation potential than the GS lasing QD lasers, [5][6][7][8][9] because of their higher modal gain and shorter carrier capture time. [9][10][11] Thus, ES lasing is expected to enhance the modulation performance of the QD lasers.…”
mentioning
confidence: 99%